2018
DOI: 10.1111/gcb.14109
|View full text |Cite
|
Sign up to set email alerts
|

Warming weakens facilitative interactions between decomposers and detritivores, and modifies freshwater ecosystem functioning

Abstract: Warming is among the major drivers of changes in biotic interactions and, in turn, ecosystem functioning. The decomposition process occurs in a chain of facilitative interactions between detritivores and microorganisms. It remains unclear, however, what effect warming may have on the interrelations between detritivores and microorganisms, and the consequences for the functioning of natural freshwater ecosystems. To address these gaps, we performed a field experiment using tank bromeliads and their associated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 107 publications
(211 reference statements)
4
25
0
Order By: Relevance
“…The stronger influence of bacteria, relative to macroinvertebrates, on decomposition in the Brazilian restinga may be a result of the drier, warmer conditions than the other sites, influencing both leaf litter digestibility and microbial metabolic rates, and has recently been supported in manipulative experiments (Bernabé et al. ).…”
Section: Discussionmentioning
confidence: 90%
“…The stronger influence of bacteria, relative to macroinvertebrates, on decomposition in the Brazilian restinga may be a result of the drier, warmer conditions than the other sites, influencing both leaf litter digestibility and microbial metabolic rates, and has recently been supported in manipulative experiments (Bernabé et al. ).…”
Section: Discussionmentioning
confidence: 90%
“…Environmental bacterial reservoirs may be particularly important to the microbiomes of aquatic hosts because the whole organism is in continual contact with bacteria in the water column [9]. Biotic community interactions are important drivers of environmental bacterial community structure [10,11]. For example, invertebrate detritivores are closely associated with environmental bacteria in aquatic ecosystems, and together they play a pivotal role in ecosystem functions such as detritus processing and nutrient cycling, with invertebrates both consuming and providing nutrients to bacterial communities [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…Biotic community interactions are important drivers of environmental bacterial community structure [10,11]. For example, invertebrate detritivores are closely associated with environmental bacteria in aquatic ecosystems, and together they play a pivotal role in ecosystem functions such as detritus processing and nutrient cycling, with invertebrates both consuming and providing nutrients to bacterial communities [10,12]. However, the cascading effects of these biotic interactions on host microbiome structure and pathogen resistance are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Also, changes in the litter N:P ratios can influence the survivorship (Migliorini, Srivastava, & Romero, 2018) and performance of aquatic insects living in tank bromeliads (González, Romero, & Srivastava, 2014). Tank bromeliads have been successfully used as natural microcosms to investigate the isolated impacts of environmental changes, such as rainfall regimes, warming and productivity, on community structure and ecosystem functioning (Amundrud & Srivastava, 2016;Antiqueira, Petchey, & Romero, 2018;Bernabé et al, 2018;Dézerald, Céréghino, Corbara, Dejean, & Leroy, 2015;Pires et al, 2016). These studies have reported that decreases in rainfall amount and more consecutive dry days lead to less dilution and leaching of nutrients from bromeliad phytotelmata (Richardson et al, 2000), concentrating the nutrients inside the tank.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, due to the fact that bromeliad water derives from rainwater (Kitching, 2004), rises in rainfall will increase the water volume of the ecosystem, and reduce the risk of drought (Amundrud & Srivastava, 2016;Dézerald et al, 2015), increasing habitat availability for colonisation by new organisms (Srivastava, 2006). Such an increase is expected to stimulate an increase of zooplankton density and macroinvertebrate abundance, which, in turn, could trigger predation pressure upon bacteria populations (Bernabé et al, 2018), thus decreasing their density even more. Some of these changes will have a positive effect on ecosystem functioning by enhancing litter decomposition and N flux (Prediction 2).…”
Section: Introductionmentioning
confidence: 99%